Mollusk Assemblages As Records of Past and Present Ecological Status - Dietl, Gregory P.; Durham, Stephen R.; Smith, Jansen A.; Tweitmann, Annalee (Frontiers in Marine Science, 2016)
AMBI and Bentix are widely used benthic indices for guiding remediation decisions under two major pieces of environmental legislation in Europe — the Water Framework Directive (WFD) and the Marine Strategy Framework Directive (MSFD). These indices usually incorporate all marine benthic invertebrates in a sample. Some recent studies, however, have applied these benthic indices to only mollusk species due to the ease of identifying only one taxonomic group to the species level and because death assemblages (accumulated dead mollusk shells in sediments) may be valuable sources of data for assessing baseline conditions. Although they found that ecological status differences can be detected by applying AMBI and Bentix to mollusks, these studies did not test whether mollusk-only index values, and the ecological statuses indicated by them, are equivalent to those calculated from the whole benthic community. To test this assumption, we performed a meta-analysis of data from 12 European benthic community studies comparing mollusk-only index values with whole-community values. Using five mollusk-only data sets, we also assessed whether application of AMBI and Bentix to molluscan death assemblages can be used to detect changes in ecological status over time. We show that the application of AMBI and Bentix to only the molluscan taxa in benthic communities is a viable method for determining the ecological status of water bodies. Our results also suggest that the application of benthic indices to molluscan death assemblages has great potential to 1) establish baseline conditions for assessing ecological status under the WFD and 2) estimate the natural range of variation of ecosystem attributes for defining sustainability thresholds under the MSFD. We outline three recommendations for the future use of mollusk-only AMBI and Bentix based on our results: 1) mollusk-only index values should be adjusted to facilitate comparisons with whole-community studies; 2) local ecological group assignments should be used if possible; and 3) we encourage collaboration between paleoecologists and benthic ecologists to facilitate interpretations of index values from death assemblages. We conclude that mollusk-only benthic index assessments of molluscan death assemblages have the potential to be a powerful tool for guiding management decisions under the WFD and MSFD.